How much is enough? : - McCurdy, Diane (John Wiley & Sons, 2005)
Questions concerning retirement savings abound, but the one question on everyone’s mind is, "How much is enough to provide for the type of retirement I want?" How Much Is Enough? provides the answer by helping readers build a customized plan. Author and financial planning expert Diane McCurdy clearly explains how to save on taxes and invest wisely, so that readers can find the money they need to reach their retirement goals. Readers will also learn how to comfortably work with financial advisors and manage the investments needed for retirement. Filled with in-depth insight and practical advice, How Much Is Enough? is a refreshing approach to defining retirement goals and building a personalized plan to reach them.